2005
DOI: 10.1161/01.res.0000163980.55495.44
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Disruption of TGF-β–Smad3 Signaling Leads to Enhanced Neointimal Hyperplasia With Diminished Matrix Deposition in Response to Vascular Injury

Abstract: Abstract-The role of transforming growth factor (TGF)-␤ and its signal in atherogenesis is not fully understood. Here, we examined mice lacking Smad3, a major downstream mediator of TGF-␤, to clarify the precise role of Smad3-dependent signaling in vascular response to injury. Femoral arteries were injured in wild-type and Smad3-null (null) male mice on C57Bl/6 background. Histopathological evaluation of the arteries 1 to 3 weeks after the injury revealed significant enhancement of neointimal hyperplasia in nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 61 publications
6
49
2
Order By: Relevance
“…9,10,12 However, the role of SMAD3 in the vasculature is somewhat less clear. As reported by Kobayashi et al, 49 Smad3 null mice showed enhanced neointimal hyperplasia with decreased matrix deposition in response to femoral artery injury.…”
Section: 43supporting
confidence: 64%
“…9,10,12 However, the role of SMAD3 in the vasculature is somewhat less clear. As reported by Kobayashi et al, 49 Smad3 null mice showed enhanced neointimal hyperplasia with decreased matrix deposition in response to femoral artery injury.…”
Section: 43supporting
confidence: 64%
“…16 In the vascular system, TGF-␤ inhibits the proliferation of endothelial cells while it stimulates that of the adjacent smooth muscle cells, 33,34 despite their close proximity. Conversely, it has a pro-apoptotic effect on endothelial cells while being anti-apoptotic in smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…36 Interestingly, partial TGF-␤ pathway inhibition in Smad3-null mice enhanced SMC proliferation and intimal thickening in a mouse femoral artery injury model. 37 Although the biological response in the mouse femoral model differs somewhat from that of the rat in carotid injury, it may be that inhibition of the entire TGF-␤ signaling pathway via TGF-␤ ligand or receptor activity is preferred for preventing vascular fibrosis.…”
Section: Discussionmentioning
confidence: 99%